Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Elsa DORLIN - Se défendre - Une philosophie de la violence - UPOP Marseille (2020)
Se défendre. Une philosophie de la violence Conférence d’Elsa DORLIN En 1685, le Code noir défendait « aux esclaves de porter aucune arme offensive ni de gros bâtons » sous peine de fouet. Au XIXe siècle, en Algérie, l’État colonial interdisait les armes aux indigènes, tout en accordant aux colons le droit de s’armer. Aujourd’hui, certaines vies comptent si peu que l’on peut tirer dans le dos d’un adolescent noir au prétexte qu’il était « menaçant ». Une ligne de partage oppose historiquement les corps « dignes d’être défendus » à ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce « désarmement » organisé des subalternes pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Des résistances esclaves au ju-jitsu des suffragistes, de l’insurrection du ghetto de Varsovie aux Black Panthers ou aux patrouilles queer, Elsa Dorlin retrace une généalogie de l’autodéfense politique. Sous l’histoire officielle de la légitime défense affleurent des « éthiques martiales de soi », pratiques ensevelies où le fait de se défendre en attaquant apparaît comme la condition de possibilité de sa survie comme de son devenir politique. Cette histoire de la violence éclaire la définition même de la subjectivité moderne, telle qu’elle est pensée dans et par les politiques de sécurité contemporaines, et implique une relecture critique de la philosophie politique, où Hobbes et Locke côtoient Frantz Fanon, Michel Foucault, Malcolm X, June Jordan ou Judith Butler.
Keywords: antiracisme; approches et analyses; cours; discipline; militance; patriarcat; philosophie; pol5480; premier cycle; racisme; ressource en ligne; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

Notes toward a performative theory of assembly - Butler, Judith (Harvard University Press, 2015)
Judith Butler elucidates the dynamics of public assembly under prevailing economic and political conditions, analyzing what they signify and how. Understanding assemblies as plural forms of perfomative action, Butler extends her theory of performativity to argue that precarity - the destruction of the conditions of livability - has been a galvanizing force and theme intoday's highly visible protests.
Keywords: approches et analyses; corps; discipline; genre; inégalités; militance; performativité; philosophie; précarité; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques

The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

Les rabat-joie féministes (et autres sujets obstinés) - Ahmed, Sara (Cahiers du Genre, 2012)
Interrogeant la figure de la « féministe rabat-joie », cet article propose d’en explorer la négativité, aussi bien que la capacité d’agir dont elle est la promesse. Il s’agit ainsi, en repositionnant la pensée féministe comme critique de l’injonction au bonheur, de comprendre le sujet féministe en tant que sujet obstiné. L’obstination féministe est alors appréhendée comme le socle incertain d’une politique collective traduisant les émotions individuelles, la douleur ou la colère ressentie face aux injustices. Au-delà, la figure du sujet obstiné permet de saisir la façon dont, au sein des espaces féministes, les femmes noires ont pu être réduites à leur colère et désignées comme cause des divisions engendrées par le racisme. La position de sujet obstiné constituerait ainsi autant un lieu de tensions que de revendications politiques. https://www.saranahmed.com/
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; care; cours; discipline; europe; fem1000; féminismes noirs; incontournable; intersectionnalité; luttes; militance; occident; orient; philosophie; phénoménologie; politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Pornography embodied: from speech to sexual practice - Mason-Grant, Joan (Feminist constructions, 2004)
What does it mean to conceptualize pornography as a material practice rather than as speech? Mason-Grant argues that this idea, fundamental to the work of Andrea Dworkin and Catharine MacKinnon, has been obscured in legal wrangling and political polarization over their civil ordinance. Within the arena of legal argument, where the principle of free speech holds sway for progressive thinkers, their analysis of pornography is rendered, at worse, an apology for censorship and, at best, an argument about the social force of speech, rather than recognized as a fundamental challenge to the very idea of pornography as speech. In this book, Mason-Grant first shows how the persistent 'speech paradigm' inevitably obscures the innovative core of the Dworkin-MacKinnon critique of mainstream pornography. She then develops an alternative 'practice paradigm' that critically engages their analysis, capturing and extending its core insights about the role of pornography in sexual practice. Drawing on phenomenology of the lived body, this alternative paradigm provides a way of re-thinking how the pervasive use of mass-market heterosexual pornography contributes to the cultivation of an embodied and tacit sexual know-how that is subordinating, and raises important questions about alternative materials produced and used by sexual minorities. In her conclusion, Mason-Grant considers the implications of her analysis not for law, but for a critical pedagogy in youth sexuality education.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme pop; hétérosexisme; militance; patriarcat; philosophie; phénoménologie; premier cycle; pédagogie; sciences humaines; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis